Biomarkers of delirium risk in older adults: a systematic review and meta-analysis - Lozano-Vicario, Lucía; García-Hermoso, Antonio; Cedeno-Veloz, Bernardo Abel; Fernández-Irigoyen, Joaquín; Santamaría, Enrique; Romero-Ortuno, Román; Zambom-Ferraresi, Fabricio; Sáez de Asteasu, Mikel L.; Muñoz-Vázquez, Ángel Javier; Izquierdo, Mikel; Martínez-Velilla, Nicolás (Frontiers in Aging Neuroscience, 2023)
Delirium is a neuropsychiatric syndrome associated with increased morbidity and mortality in older patients. The aim of this study was to review predictive biomarkers of delirium in older patients to gain insights into the pathophysiology of this syndrome and provide guidance for future studies. Two authors independently and systematically searched MEDLINE, Embase, Cochrane Library, Web of Science and Scopus databases up to August 2021. A total of 32 studies were included. Only 6 studies were eligible for the meta-analysis, pooled results showed a significant increase in some serum biomarkers (C-reactive protein [CRP], tumour necrosis factor alpha [TNF-α] and interleukin-6 [IL-6]) among patients with delirium (odds ratio = 1.88, 95% CI 1.01 to 1.637; I2 = 76.75%). Although current evidence does not favour the use of any particular biomarker, serum CRP, TNF-α, and IL-6 were the most consistent biomarkers of delirium in older patients.